Soil environmental quality and its assessment of rice production for non-environmental pollution in Nanhu district of Jiaxing in Zhejiang Province - LI Ai-fen; QIAN Shi-ming; LI Jin (浙江大学学报. 农业与生命科学版)
One hundred and three samples of paddy soils were taken in 2004 from Nanhu district of Jiaxing, northern Zhejiang Province for charactering concentrations of several heavy metals according to environmental requirements for origin of non-environmental pollution rice, and the environmental quality of the soils was assessed. The results show that the environmental quality of paddy soils in the district was well and suitable for rice production of non-environmental pollution. Total concentrations of As, Pb, Cr, Cd and Hg in the soils averaged 7.7, 23.7, 88.9, 0.18 and 0.22 mg·kg-1, respectively. The soils were not significantly contaminated with As and Pb. Ninty-four samples (91.3%) were qualified for soil environmental quality requirements of non-environmental pollution rice production, while nine samples were polluted by Cd and Hg. In order to secure the safety of rice production, several agricultural measurements were recommended, i.e., strengthening treatments of the polluted water and the waste, using lime to stable heavy metals, increasing the usage of phosphorus and organic fertilizers, and selecting the rice cultivars that are tolerant to heavy metals.